Predicting Retail Company Bankruptcies in the Era of COVID - Campbell, Annhenrie; Lindsay, David H.; Soydemir, Gökçe; Tan, Kim B. (Journal of Marketing Development and Competitiveness, 2024)
Trade journals and the popular press have suggested that the COVID-19 pandemic precipitated a second “retail apocalypse.” The current study tests whether pre-pandemic data can be used to predict COVID-19 retail firm bankruptcies using a chaos-based model. This study successfully uses a chaos statistic calculated from stock market time-series returns for pair-match retail firms prior to the pandemic to predict bankruptcies occurring shortly afterwards.